Carbs spike lunchtime glucose - (:unkn) unknown (My University, 2021)
This is a weekly Q and A newspaper column under the byline of Dr. Kathy Kolasa. Today's column discusses continuous glucose monitoring, insulin resistance, and yogurts with lower carbohydrate contents.
Medical and dietetic students often co-author a column for the Daily Reflector under Dr. Kolasa's byline. The students research the topic a reader or patient has asked. Dr. Kolasa reviews their draft for technical accuracy, patient friendly language, people first language. She fact checks the study or other evidence-based reference the student provides. If a physician review is appropriate, Dr. Kolasa requests a colleague from ECU physicians to review the article. The final draft is submitted to the Reflector with the editor having the final say. The headline is written by the Reflector headline writer. The food and nutrition column has run weekly since 1987. Starting in 2020, in addition to the Daily Reflector, the article is published in daily and weekly papers owned by the Adams Publishing Group East (https://adamspg.com)
Keywords: Medicine, Nutrition, continuous glucose monitoring, insulin resistance, CGM